Assessment of Hygiene Degradation and Expiry Indicators in Household Bedding Products - Ravikant Nanwatkar; Rasika Raut; Itkikar Hirkani; Samruddhi Bhadke (International Journal of Environmental Noise and Pollution Control, 2026)
Household bedding products such as pillows, bedsheets, blankets, and mattresses play a crucial role in ensuring comfort, sleep quality, and overall health. However, prolonged use without timely replacement or proper maintenance can result in hygiene degradation, leading to the accumulation of dust, allergens, microorganisms, and chemical wear. This study aims to assess the factors contributing to hygiene decline and to identify reliable indicators of expiry for common bedding items. The research explores textile durability, microbial growth patterns, moisture retention, and material wear as determinants of bedding lifespan. Through literature review, user surveys, and laboratory analyses, the study evaluates how usage frequency, cleaning practices, and environmental conditions accelerate hygiene deterioration. Special emphasis is placed on recognizing visible and non-visible indicators of expiry, such as fabric thinning, odor retention, loss of elasticity, and microbial contamination levels. Findings suggest that regular monitoring of these parameters can support evidence-based replacement guidelines, contributing to improved sleep hygiene and reduced health risks. The paper also discusses sustainable approaches to disposal and recycling, aligning bedding management with environmental responsibility. Overall, this study provides a framework for identifying expiry and hygiene thresholds, thereby enhancing household health practices and consumer awareness. The study also examines the physicochemical alterations that bedding fibers undergo with time, such as decreased moisture-wicking ability, fiber breakage, and decreased tensile strength. In order to simulate long-term home use, laboratory simulations were carried out. This allowed for the controlled monitoring of microbial proliferation under various temperature and humidity conditions. The results of the survey also showed that consumers were generally unaware of the health risks associated with prolonged bedding usage and the suggested replacement intervals. A comparison of natural and synthetic materials reveals variations in their resilience to microbial colonization, durability, and allergen retention.
Keywords: Absorbent hygiene product waste; Environmental impact; Life Cycle Assessment; Waste management improvement; recycling